2022
DOI: 10.3389/fmolb.2022.991641
|View full text |Cite
|
Sign up to set email alerts
|

Aging RNA granule dynamics in neurodegeneration

Abstract: Disordered RNA-binding proteins and repetitive RNA sequences are the main genetic causes of several neurodegenerative diseases, including amyotrophic lateral sclerosis and Huntington’s disease. Importantly, these components also seed the formation of cytoplasmic liquid-like granules, like stress granules and P bodies. Emerging evidence demonstrates that healthy granules formed via liquid-liquid phase separation can mature into solid- or gel-like inclusions that persist within the cell. These solidified inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…A recent study identified IP 7 kinase PPIP5K as an α-synuclein neurotoxicity modulator by functional RNAi screening using nematode Perkinson's disease model ( 27 ). Moreover, IP6K and IP 7 facilitate the formation of aberrant protein-RNA aggregates inducing neurotoxicity in various neurodegenerative disorders ( 28 ) at least via promoting the interaction of RNA-binding proteins (for IP6K) and inhibiting the 5′-decapping reaction of non-translated mRNAs (for IP 7 ) ( 29 , 30 ). In addition, IP 7 competitively binds to AKT and inhibits its downstream signaling including mTOR, a key regulator of cell survival ( 31 , 32 ) (Information of proteins associating with IP 6 was summarized in Supplementary Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified IP 7 kinase PPIP5K as an α-synuclein neurotoxicity modulator by functional RNAi screening using nematode Perkinson's disease model ( 27 ). Moreover, IP6K and IP 7 facilitate the formation of aberrant protein-RNA aggregates inducing neurotoxicity in various neurodegenerative disorders ( 28 ) at least via promoting the interaction of RNA-binding proteins (for IP6K) and inhibiting the 5′-decapping reaction of non-translated mRNAs (for IP 7 ) ( 29 , 30 ). In addition, IP 7 competitively binds to AKT and inhibits its downstream signaling including mTOR, a key regulator of cell survival ( 31 , 32 ) (Information of proteins associating with IP 6 was summarized in Supplementary Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…RBPs such as TDP-43, FUS, and hnRNPA1/A2 are normally localized in the nucleus in a soluble single-state phase, where they bind with RNA and shuttle continuously between the nucleus and cytoplasm [47]. Unfortunately, when RBPs are mislocalized in the cytoplasm, insoluble solid pathological aggregates thus take shape and participate in the formation of stress granules (SGs), as several studies have suggested [83,84]. These aggregates not only impair neuronal homeostasis and disrupt the regulation of nuclear RNA processing but also trigger several dysfunctions, such as mitochondrial dysfunction and inflammation.…”
Section: Rna-binding Protein Llps: Tdp-43 and Fus As Paradigms In Als...mentioning
confidence: 99%
“…We also understand little about how the compositional heterogeneity changes over time within individual condensate entities. For example, stress granules appear to contain distinct subproteomes under different stresses (Aulas et al, 2017;Markmiller et al, 2018) and can mature into solid-or gel-like inclusions that persist within the cell in neurodegenerative diseases (Rhine et al, 2022). At least 238 proteins have been curated to reside in stress granules (Markmiller et al, 2018).…”
Section: Understanding the Origins And Functional Implications Of Het...mentioning
confidence: 99%